Peran Kesadaran Pajak Dalam Peningkatan Kepatuhan Pajak Melalui Pengetahuan Dan Sanksi Pajak - Retnaningtyas Widuri; Michella Shan Christabel; Evelyn Lavinia (Universitas Trunojoyo Madura, 2024)
This research aims to analyze the influence of tax knowledge and tax sanctions on tax compliance as well as the mediating role of tax awareness, related to the phenomenon that there are still many taxpayers who do not have compliance with their tax obligations, while a poor level of tax compliance can be a loss for the state. This research uses a survey method with a questionnaire base developed from several previous researchers, involving taxpayers who are MSME actors in the e-commerce sector spread across Indonesia. The number of respondents involved in this research was 117 people, with the criteria being taxpayers of MSMEs in the e-commerce sector. This research uses the Partial Least Square technique to carry out data analysis through the Warp Partial Least Square (Warp-PLS) application. The research results show that tax knowledge has a positive influence on tax compliance, while tax sanctions have no effect on tax compliance. Furthermore, it was also found that tax awareness was able to mediate the influence of tax knowledge and tax sanctions on tax compliance.